Pengelolaan Kebun Induk Kelapa Sawit (Elaeis guinensis Jacq.) pada Lahan Suboptimal di PT Binasawit Makmur - Frengky Mario Rafael Sirait; Mochamad Suwarno; Budi Wahyono; Zulhermana Sembiring; Dwi Asmono (Seminar Nasional Lahan Suboptimal, 2018)
Sirait et al, 2019. Maintaining of Seed Garden for Suboptimal Area in PT Binasawit Makmur. pp. 360-365.   Continual improvement of seed production is very important to fulfill of oil palm sprouts demand. To fulfill that demand, suboptimal land factor that so far being limiting factors should be minimized so that’s not to inhibit the production of oil palm seeds. This reasearch aim was maintaining of seed garden for suboptimal area  in PT Binasawit Makmur.  PT. Binasawit Makmur, Sampoerna Agro Tbk. is one of the seed producers in Indonesia which has the selected Dura mains planted on suboptimal land were located on Mesuji Districts, Ogan Komering Ilir Regency, South Sumatera Province. Maintaining of Dura palm strategy is needed by stricty Quality Control of processes and environmental conditions in the field to produce quality seeds. Optimalization of seed production on sub-optimal land are by adding organic matter to the soil and applying irrigation systems to the selected elite Dura palms. The addition of organic matter and applying of irrigation systems can made continuity of seed production with optimal quality and quantity so that the demand for oil palm sprouts for custumer satisfaction.